2022
DOI: 10.21789/24222704.1786
|View full text |Cite
|
Sign up to set email alerts
|

Ocupaciones y salarios públicos en la segunda mitad del siglo XIX. El caso de Uruguay, c. 1853-1893

Abstract: Este artículo analiza el sector público en Uruguay entre 1853 y 1893 a partir de las funciones estatales, las categorías ocupacionales y los niveles salariales por nivel de calificación. El enfoque de este trabajo se basa en un análisis general sobre la estructura de empleo y en una selección de ocupaciones. Los resultados indican la participación relativamente elevada de empleos de baja calificación y una mayor compensación de acuerdo al grado de calificación, independientemente de la función estatal. En térm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Bruns-Smith et al [48], in a study in the USA covering 100 resorts and 120,000 clients, found a very weak relationship between the implementation of environmental improvement programs and increases in customer satisfaction. Therefore, the adoption of certification systems such as those mentioned does not necessarily translate into improvements in reputations that produce business benefits, therefore, the decision on which programs to implement should be based on an individualized cost-benefit analysis of each program [49]. In this sense, businesspersons of Puerto Vallarta are aware that the CE certification for their companies would produce benefits; however, they are not willing to invest, mainly because of the additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…Bruns-Smith et al [48], in a study in the USA covering 100 resorts and 120,000 clients, found a very weak relationship between the implementation of environmental improvement programs and increases in customer satisfaction. Therefore, the adoption of certification systems such as those mentioned does not necessarily translate into improvements in reputations that produce business benefits, therefore, the decision on which programs to implement should be based on an individualized cost-benefit analysis of each program [49]. In this sense, businesspersons of Puerto Vallarta are aware that the CE certification for their companies would produce benefits; however, they are not willing to invest, mainly because of the additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…En el ámbito político e institucional implicó transformaciones en los instrumentos estatales y en la propia consolidación del Estado. Durante el período se construyeron herramientas de intervención estatal vinculadas con el establecimiento de mecanismos de coerción profesional (códigos de comportamiento y cuerpos profesionales tecnificados) y se desarrolló la infraestructura acuática, terrestre y telefónica; por otra parte, se implementaron mecanismos de intervención social como la reforma educativa, las primeras medidas de sanidad pública y la secularización con respecto a la Iglesia (Martínez-Rodríguez, 2021, 2022.…”
Section: Introductionunclassified